The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12916-021-02064-8
|View full text |Cite
|
Sign up to set email alerts
|

Renal function and lipid metabolism are major predictors of circumpapillary retinal nerve fiber layer thickness—the LIFE-Adult Study

Abstract: Background Circumpapillary retinal nerve fiber layer thickness (cpRNFLT) as assessed by spectral domain optical coherence tomography (SD-OCT) is a new technique used for the detection and evaluation of glaucoma and other optic neuropathies. Before translating cpRNFLT into clinics, it is crucially important to investigate anthropometric, biochemical, and clinical parameters potentially affecting cpRNFLT in a large population-based dataset. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 67 publications
1
14
0
3
Order By: Relevance
“…In our subanalysis, pRNFL thickenss of superior quadrant, inferior quadrant, average pRNFL, CST, average macular thickness and GC-IPL showed significant positive correlation with eGFR. Renal dysfunction has also been correlated with decreased choroidal thickness [ 39 ] and pRNFL thickness [ 46 48 ]. This may partly be attributed to the sympathetic nervous system overactivation which is characteristic of CKD [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our subanalysis, pRNFL thickenss of superior quadrant, inferior quadrant, average pRNFL, CST, average macular thickness and GC-IPL showed significant positive correlation with eGFR. Renal dysfunction has also been correlated with decreased choroidal thickness [ 39 ] and pRNFL thickness [ 46 48 ]. This may partly be attributed to the sympathetic nervous system overactivation which is characteristic of CKD [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intraocular pressure was measured using an ocular response analyzer (Reichert, Depew, NY). The covariates were selected based on prior knowledge and previous literature [12,14,18].…”
Section: Assessment Of Covariatesmentioning
confidence: 99%
“…This may be because this relationship has not been clari ed in different populations, such as healthy individuals and those with diabetes or hypertension. In addition, most studies on this topic have been cross-sectional, no longitudinal population-based studies have been conducted, but this approach is needed to unravel the causal relationship between these factors [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] Previous studies have reported associations between circulating metabolites and alterations in neuroretinas, but these are limited to single-biomarker approaches. [21][22][23] Additionally, these studies majorly focused on the RNFL (representing axons of retinal ganglion cells [RGCs]), while growing evidence suggesting that GCIPL (representing cytosol and dendrites of RGCs) is a more sensitive and reproducible mirror for neuroretinal damage and systemic health. 6,[24][25][26] We hypothesized that circulating metabolites may underlie the links between neuroretinal changes and systemic health.…”
Section: Introductionmentioning
confidence: 99%